Why Korea's Youth Unemployment Rate Rises - Kyungsoo Choi (Korea Development Institute (KDI), 2017)
Korea's youth unemployment rate has rapidly ascended since 2013 while total unemployment remains little changed. The youth unemployment rate of high school graduates has been maintained at a stable level thanks to the growing number of service jobs. However, a rapidly rising number of college graduates are unemployed due to the slow creation of professional and semi-professional jobs. The government's youth employment support program has also contributed to the increase, but the extent is minor. To enhance the demand for skilled workers, economic innovation needs to accelerate and excellence in higher education must be achieved. - The youth (15-29) unemployment rate rapidly ascended from 2013. - The decline in the employment rate for men aged 25-29 stopped after 2009 while the unemployment rate has soared since 2013. - Youth employment is driven more by future careers than income. - The skill level of young Koreans is densely concentrated in the middle, which means that their skill level is high among the bottom but low among the top. - Advanced economies experienced a severe polarization of jobs in the 1980s, an increase in service jobs from the 1990s with the IT revolution, followed by a decrease in skilled jobs in recent years. - The impact from the demographic changes to the youth unemployment rate is insignificant as of now, but the population aged 25-29 is expected to rise by 390,000 in 2017-2021. - The Ministry of Employment and Labor's Employment Success Package Program partially increases the unemployment rate but with little significance. - With growing service jobs from 2010, the employment rate and the wages of high school graduates improved. - To increase service jobs, the gains from technological innovation must lead to a reduction in prices. But, this is only possible when regulations are eased and competition is encouraged. - The minimum wage system does not directly increase the wages of high school graduates, but it can serve as an institutional tool necessary for the protection of labor conditions. - The rising youth unemployment rate is driven by the increase in the unemployment rate of college graduates, particularly due to the decrease in semi-professional jobs. - Korea's innovation level must be enhanced to increase the number of skilled jobs. To that end, an environment must be created to motivate innovation, business growth dynamism and excellence in education.
Keywords: 330